Aesthetics and Architecture: Living is the answer. - Alison, Aurora (Scenari, 2021)
This paper wants to focus the main topics of inhabiting in three dimensions concerning the relationship between Aesthetics and Architecture: 1) The intimate space of the house, 2) The shared space of the city and 3) The felt space of Atmospheres. In this way we would like to introduce the concept of lived space as an important field of the Architecture project and, at the same time, we would like to illustrate how Architecture approaches the world of phenomenological and aesthetically sensitive inhabiting space.